Management Practicesd and MSME Performance in North Sumatra Province - Abdi Tanjung; Mara Judan Rambey; Toharuddin Harahap; Abdul Latif Lubis (PT. Hanken SUkses Jaya, 2023)
From the results of my research, there is a relationship between management practices and the performance of SMEs in Indonesia in the 2017-2021 period. data collection technique using a data collection linking survey data on management practices with company performance data from official Indonesian business registers. In this research, it was found that MSMEs tend to use formal management practices rather than large companies. However, the practice appears to have real benefits for the MSMEs that use it, as it is positively linked to the survival, growth, and productivity of firms. The results of this study add to policy initiatives that seek to encourage MSMEs to improve management skills and abilities in business.